Desain Sepatu untuk Penderita Diabetes - Hillary Paays; Taufiq Panji Wisesa (Penerbit Itenas, 2026)
The development of specialized footwear for individuals with diabetes plays a crucial role in advancing modern healthcare products. Beyond aesthetics, these designs must address key factors such as ergonomics, thermal comfort, and the prevention of diabetic foot ulcers, which are highly prevalent due to vascular complications and peripheral neuropathy. This study employed a questionnaire-based approach to gather direct input from diabetic patients regarding their preferences and specific needs, providing essential insights for designing optimal footwear solutions. Based on responses from fifty participants, comfort, soft cushioning, and breathable materials emerged as the most critical features. To effectively minimize the risk of infection and open wounds, footwear must offer excellent ventilation and significantly reduce plantar pressure. The design process involved an in-depth analysis of user requirements, combined with the evaluation of various materials such as EVA foam, suede, and traditional jarik fabric known for its superior breathability. A key innovation introduced in this prototype includes a combination of highly breathable materials, memory foam insoles that adapt to the individual’s foot contour, and an outsole featuring a 3D-printed auxetic lattice structure engineered for optimal pressure distribution. The design was also developed using ergonomic principles and foot anthropometry, incorporating Indonesian adult foot dimension data to ensure optimal fit and comfort.